Breath-Hold Diving – The Physiology of Diving Deep and Returning - Patrician, Alexander; Dujić, Željko; Spajić, Boris; Drviš, Ivan; Ainslie, Philip N. (Frontiers in Physiology, 2021)
Breath-hold diving involves highly integrative physiology and extreme responses to both exercise and asphyxia during progressive elevations in hydrostatic pressure. With astonishing depth records exceeding 100 m, and up to 214 m on a single breath, the human capacity for deep breath-hold diving continues to refute expectations. The physiological challenges and responses occurring during a deep dive, highlight the coordinated interplay of oxygen conservation, exercise economy and hyperbaric management. In this review, the physiology of deep diving is portrayed as it occurs across the phases of a dive: the first 20 m; passive descent; maximal depth; ascent; last 10 m and surfacing. The acute risks of diving (i.e. pulmonary barotrauma, nitrogen narcosis and decompression) and the potential long-term medical consequences to breath-hold diving are summarized, and an emphasis on future areas of research of this unique field of physiological adaptation are provided.